Deep insight into ionic transport in polyampholyte gel electrolytes towards high performance solid supercapacitors. Issue 27 (26th June 2019) - Li, Dong; Xu, Zhen; Ji, Xingxiang; Liu, Libin; Gai, Guangjie; Yang, Jianbo; Wang, Jijun
Abstract : A novel polyampholyte gel electrolyte with high ionic conductivity and high mechanical strength was developed and was suitable for supercapacitors. Abstract : Gel polymer electrolytes with high ionic conductivity and reasonable mechanical strength are highly desired. To address this, deep understanding of the ionic transport pathway and conductivity mechanism in gel electrolytes is very important. Here, a series of polyampholyte gel electrolytes were synthesized and ionic conductivity mechanisms at different salt concentrations were proposed. At low LiCl concentration, molecular clusters due to electrostatic interactions between anions and cations and hydrogen bonds between molecular chains and surrounding water molecules exist, while at high LiCl concentration, Li + (H2 O)2 clusters are present in the gel electrolyte. Both of the clusters result in low ionic conductivity. By controlling the monomer ratio and LiCl concentration, the polyampholyte gel electrolyte exhibits high mechanical strength with a high ionic conductivity of ∼8.2 mS cm −1 . Importantly, the interfacial resistance between the electrode and electrolyte is highly reduced by in situ copolymerization of anionic and cationic monomers in the presence of an activated carbon (AC) electrode. The AC electrode with an in situ polymerized electrolyte has a high areal specific capacitance of 297 mF cm −2 at 0.8 mA cm −2 and can retain 70% of its capacitance after 7000 cycles. The assembled solid supercapacitor not only possesses a high areal energy density of 6.6 mW h cm −2 and power density of 2.4 W cm −2, but also reveals good self-healing ability. Our work provides a fundamental revelation of gel electrolytes and the obtained novel polyampholyte gel electrolytes have potential for practical applications in energy storage devices.